2019
DOI: 10.2147/jpr.s176960
|View full text |Cite
|
Sign up to set email alerts
|

<p>Therapeutic efficacy and safety of radiofrequency ablation for the treatment of trigeminal neuralgia: a systematic review and meta-analysis</p>

Abstract: ObjectiveThe objective of this study was to summarize the effectiveness and safety of trigeminal neuralgia (TN) treatment via different radiofrequency approaches such as continuous radiofrequency (CRF), pulsed radiofrequency (PRF), and combined CRF and pulsed radiofrequency (CCPRF) treatments, thus providing high-quality clinical evidence for TN treatment.MethodsA series of databases were searched for relevant articles published between January 1998 and April 2018. The modified Jadad scale was referred to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 29 publications
3
28
0
5
Order By: Relevance
“…ese findings suggested that with high temperature of Table 3: Numbness degree on day 1 and at 2 y after operation between the two groups (n(%)). [15][16][17]. In this study, high temperature (95°C) was adopted for radiofrequency therapy to reduce thermal attenuation caused by the distance from the radiofrequency target and target nerve, which in turn leads to incomplete nerve destruction and high relapse rate.…”
Section: Discussionmentioning
confidence: 99%
“…ese findings suggested that with high temperature of Table 3: Numbness degree on day 1 and at 2 y after operation between the two groups (n(%)). [15][16][17]. In this study, high temperature (95°C) was adopted for radiofrequency therapy to reduce thermal attenuation caused by the distance from the radiofrequency target and target nerve, which in turn leads to incomplete nerve destruction and high relapse rate.…”
Section: Discussionmentioning
confidence: 99%
“…A new method (CCRF, combined application of CRF and PRF) consisting of the application of conventional and pulsed radiofrequency in one procedure has been reported in the recent years. According to some authors, this technique is considered to be an equally effective and safe method of pain treatment in trigeminal neuralgia [24,25].…”
Section: Radiofrequency Applicationmentioning
confidence: 99%
“…Imaging techniques have developed significantly in the recent years and computed tomography (CT) is applied alongside fluoroscopy, as well as semi-conductor laser locators and 3D-printed template guidance. This allows the procedure to be shortened significantly and increases the comfort and the safety of the patient during the procedure [24].…”
Section: Radiofrequency Applicationmentioning
confidence: 99%
See 2 more Smart Citations